2017
DOI: 10.1111/jvp.12461
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pharmacokinetics of meloxicam in horses after surgery for colic syndrome

Abstract: NSAIDs are often used in horses with colic syndrome during the postoperative period, due to their ability to contrast endotoxemia and to promote an analgesic and anti-inflammatory effect. As the pharmacokinetics of a drug are often modified in unhealthy animals compared to healthy subjects, the aim of this study was to evaluate the pharmacokinetic profile of meloxicam after i.v. administration in horses undergoing laparotomy for colic syndrome. Eight horses received 0.6 mg/kg of meloxicam i.v. towards the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Pharmacokinetic results for the intravenous formulation were similar to those reported previously . Protein binding analysis yielded that meloxicam was highly bound to plasma proteins.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Pharmacokinetic results for the intravenous formulation were similar to those reported previously . Protein binding analysis yielded that meloxicam was highly bound to plasma proteins.…”
Section: Discussionsupporting
confidence: 82%
“…Several formulations are marketed for equids both adults and foals in Europe, Australia, and New Zealand . At this time, pharmacokinetic (PK) studies in healthy and postoperative animals have been only reported for intravenous and oral routes, specifically suspension and tablets (off‐label use) formulations . On the other hand, PK parameters of a granule oral formulation, which is used in equine practice in Europe, Australia, and New Zealand, have not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical trial demonstrated that flunixin provided superior analgesia in the post‐operative period of horses that had undergone surgery to correct strangulating small intestinal lesions even when meloxicam was used twice daily . Pharmacological studies suggest that an increased dosing frequency is unnecessary in the post‐surgical colic and that higher doses used in this study may offset any potential benefits of COX‐2 selectivity. In an experimental model of colic, in which NSAIDs were administered before the ischaemic model of colic was induced, there was no difference in pain score between horses given meloxicam or flunixin in the 24‐h post‐operative period.…”
Section: Resultsmentioning
confidence: 80%
“…The aim of this study by A. Di Salvo and colleagues in Italy and South Korea was to evaluate the pharmacokinetic profile of meloxicam after intravenous administration in horses undergoing laparotomy for colic syndrome .…”
Section: Pharmacokinetics Of Meloxicam After Colic Surgerymentioning
confidence: 99%